Efektivitas Program Keluarga Berencana Pada Dinas Pengendalian Penduduk Dan Keluarga Berencana Kota Bitung Dalam Menekan Laju Pertumbuhan Penduduk Di Kota Bitung - Rompah, Junike Ketsia Olivia; Goni, Shirley Y.V.I.; Tasik, Femmy C.M. (Sam Ratulangi University, 2023)
The purpose of the study was to determine and analyze the effectiveness of the family planning program at the Bitung City Population Control and Family Planning Office in suppressing the population growth rate in Bitung City. This research was conducted in April 2023 at the Bitung City Population Control and Family Planning Office. This research uses qualitative research methods to explore in depth the problems that occur. The instruments used were direct observation in the field, literature and in-depth interviews with 8 informants. The results of research in the field, it was found that the target of the family planning program carried out by the Office of Population Control and Family Planning (DPPKB) can be said to be effective, where the targets targeted are couples of childbearing age (PUS) in Bitung City are also scattered in Bitung City, the level of public knowledge of family planning is still low, but the success of the family planning program in Bitung City can be said to be successful as seen from the number of birth rates that are still under control, population growth in Bitung City is caused not only by births but other factors such as population movements.